(untitled) (Nativa, 2018)
A presente pesquisa desenvolveu-se no âmbito do Projeto Ater “Mais Gestão”, proposto pelo Ministério do Desenvolvimento Agrário – MDA e teve como objetivo analisar o diagnóstico de 25 cooperativas da agricultura familiar localizadas no estado do Paraná. Optou-se pela análise minuciosa da área de Gestão Organizacional, pois constatou-se em estudos preliminares que esta subárea apresentou as maiores fragilidades. Tratou-se de um estudo documental, observacional e bibliográfico. Constatou-se que os principais limites se encontram nas subáreas “estrutura organizacional” e “organização do quadro social”, e as potencialidades nas subáreas “direção e participação” e “organização do quadro social”. Pondera-se também que os principais fatores que interferem na gestão organizacional das cooperativas da agricultura familiar incluem o apoio estatal, a escolha dos cooperados, a participação efetiva dos membros nas decisões e na gestão e o acesso às tecnologias, crédito e mercado. Palavras-chave: desenvolvimento, cooperativismo, economia solidária. EVALUATION OF ORGANIZATIONAL MANAGEMENT IN COOPERATIVES OF FAMILY FARMERS OF THE STATE OF PARANÁ ABSTRACT: The present research was developed in the scope of the Ater Project "More Management", proposed by the Ministry of Agrarian Development - MAD and had the objective of analyzing the diagnosis of 25 family farming cooperatives located in the state of Paraná. It was opted for the detailed analysis of the Organizational Management area, because in preliminary studies this subarea presented the greatest weaknesses. It was a documentary, observational and bibliographic study. It was found that the main limits are in the sub-areas "organizational structure" and "organization of the membership", and the potentialities in the subareas "direction and participation" and "organization of membership". The main factors that interfere in the organizational management of family farming cooperatives include state support, cooperative choice, effective participation of members in decision-making and management, and access to technologies, credit, and the market. Keywords: development, cooperativism, solidarity economy.